Risk Factors for the Occurrence of Musculoskeletal Disorders (MSDs) in Furniture Workers: Literature Review - Maharani Nusara Ardhi; Widodo Hariyono; Rosyidah, Rosyidah (Jurnal EduHealth, 2023)
Musculoskeletal complaints are one of the many complaints that often arise and are related to ergonomic problems. These complaints are caused or worsened by work activities and conditions, such as lifting movements, repetitive movements, unnatural postures, pushing or pulling movements, static work and working in confined areas. According to data from the 2018 Labor Force Survey (LFS), it shows that the prevalence rate of musculoskeletal disorders in workers is very high, namely 1,144,000 cases with a distribution of cases affecting the back of 493,000 cases, the upper limbs or neck 426,000 cases , and the lower limbs. under 224,000 cases. The aim of this research is to find out and identify risk factors that cause musculoskeletal complaints in furniture workers. The research method was carried out using a literature review. The literature search was carried out online, namely via Google Scholar and the Garuda Portal, resulting in 4 national articles. Data processing is carried out by identification, filtering, inclusion and eligibility based on article findings which are then analyzed. The data used is secondary data whose sources are obtained from scientific articles/journals, books, documents and laws. The risk factors that cause complaints of musculoskeletal disorders in furniture workers have several risk factors which are divided into two, namely individual factors and work factors. Individual factors include age, length of service, BMI, and smoking habits. Meanwhile, work factors include work posture and work attitude. The risk factors that cause serious musculoskeletal complaints are age, length of service and work posture.